7/x = y/27=-49/63
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
3:
a: (a-b+c)-(c-b-a)
=a-b+c-c+b+a
=2a
b: \(-\left(a-b\right)+\left(b-c+a\right)-\left(a+b-c\right)\)
\(=-a+b+b-c+a-a-b+c\)
\(=b-a\)
c: \(-\left(a-b-c\right)-\left(-a+b+c\right)-\left(a-b+c\right)\)
\(=-a+b+c+a-b-c-a+b-c\)
\(=-a+b-c\)
2:
a: \(12-\left(-12\right)=12+12=24\)
b: \(-\left(35-49\right)+\left(27-49\right)=-35+49+27-49\)
=-35+27
=-8
c: \(47-\left(59-63\right)+\left(63-47\right)\)
\(=47-59+63+63-47\)
=126-59
=67
d: \(-\left(-20\right)-\left(-30\right)-70\)
=20+30-70
=50-70
=-20
A)
-65.(87-17)-87.(17-65)
=-65.87-(-65).17-87.17-87.(-65)
=-(-65).17-87.17
=65.17-87.17
=17.(65-87)
=17.(-22)
=-374
B)
72.(28-49)+28.(-49-72)
= 72.28-72.49+28.(-49)-28.72
= -72.49+28.(-49)
= 72.(-49)+28.(-49)
= (-49).(72+28)
= -49.100
=-4900
C)
18-(-27)+63-(63+27)
= 18+27+63-63-27
= 45+0-27
= 45+(-27)
=45-27
=18
KICK MÌNH NHÁ
7 x 8 = 56
7 x 9 = 63
7 x 6 = 42
7 x 7 = 49
56 : 7 = 8
63 : 7 = 9
42 : 7 = 6
49 : 7 = 7
\(\frac{7}{9}\)và\(\frac{6}{7}\)có \(BC:63\)
quy đồng : \(\frac{7\times7}{9\times7}=\frac{49}{63}\)và \(\frac{6\times9}{7\times9}=\frac{54}{63}\)
\(\Rightarrow\)Đáp án là : C
C. 49/63 và 42/63
C. 49/63 và 42/63
6 x 6 = 36 63 : 7 = 9 7 x 5 = 35 6 x 7 = 42
7 x 7 = 49 48 : 6 = 8 35 : 7 = 5 42 : 6 = 7
5 x 5 = 25 49 : 7 = 7 35 : 5 = 7 42 : 7 = 6
6 x 6 = .36.... 63 : 7 = 9..... 7 x 5 = .35...... 6 x 7 = ..42...
7 x 7 = ..42... 48 : 6 = ..8... 35 : 7 = ...5.. 42 : 6 = ..7...
5 x 5 = ...25.. 49 : 7 = .7.... 35 : 5 = ...7.. 42 : 7 = ..6...
hok tốt
6 x 4 = 24 12 : 6 = 2 7 x 3 = 21 63 : 7 = 9
7 x 5 = 35 42 : 7 = 6 6 x 8 = 48 48 : 6 = 8
6 x 6 = 36 28 : 7 = 4 7 x 8 = 56 49 : 7 = 7
6 x 4 = 24 12 : 6 = 02 7 x 3 = 21 63 : 7 = 09 7 x 5 = 35 42 : 7 = 06
6 x 8 = 48 48 :6 = 8 6 x 6 = 36 28 : 7 = 04 7 x 8 = 56 49 : 7 = 07
\(7^x:49=7^{27}\)
\(7^x:7^2=7^{27}\)
\(7^x\) \(=7^{27}.7^2=7^{29}\)
Vậy x = 29
K mk mk đầu tiên nhá
7 x 8 = 56 16 : 2 = 8 36 : 6 = 6 49 : 7 = 7
2 x 5 = 10 72 : 8 = 9 9 x 3 = 27 63 : 7 = 9
6 x 4 = 24 25 : 5 = 5 4 x 8 = 32 7 x 5 = 35
7 x 8 = 56
2 x 5 = 10
6 x 4 = 24
16 : 2 = 8
72 : 8 = 9
25 : 5 = 5
36 : 6 = 6
9 x 3 = 27
4 x 8 = 32
49 : 7 = 7
63 : 7 = 9
7 x 5 = 35
Ta có -49/63=-21/27
Mà y/27=-21/27 suy ra y=-21
Lại có -21/27=-7/9
Mà 7/x=-7/9 suy ra x=-9
Vậy x=-9;y=-21
\(\frac{7}{x}=\frac{y}{27}=\frac{-49}{63}\)
Ta có:
\(\frac{7}{x}=\frac{-49}{63}\)
\(\Rightarrow-49.x=7.63\)
\(\Rightarrow-49x=441\)
\(\Rightarrow x=441:\left(-49\right)\)
\(\Rightarrow x=-9\)
\(\frac{y}{27}=\frac{-49}{63}\)
\(\Rightarrow y.63=-49.27\)
\(\Rightarrow63y=-1323\)
\(\Rightarrow y=\left(-1323\right):63\)
\(\Rightarrow y=-21\)
Vậy x = -9 ; y = -21